Psychological features of diligence at young men and girls of teenage and youthful age - Ju N Anisimova; G N Kameneva (Peoples' Friendship University of Russia (RUDN University), 2010)
In this article some psychological features of diligence at young men and girls of teenage and youthful age in the tideway of A.I. Krupnov's is complete-functional approach are considered.